Frequency and significance of indeterminate and borderline Quantiferon Gold TB IGRA results. Issue 4 (26th October 2017) - Brown, James; Kumar, Kartik; Reading, Jacob; Harvey, Jennifer; Murthy, Saraswathi; Capocci, Santino; Hopkins, Susan; Seneviratne, Suranjith; Cropley, Ian; Lipman, Marc
The Quantiferon Gold test is one of two commercially available tuberculosis (TB) interferon-γ release assays (IGRAs) recommended for the diagnosis of latent TB infection [1]. A Quantiferon Gold test is considered positive if the result is ≥0.35 IU·mL −1 [2]. However, longitudinal studies have shown that a significant number of test reversions and conversions occur if results just above or below this threshold are repeated [3, 4]. This variation may be due to random chance or other factors such as test-related errors, differences in absolute lymphocyte numbers and within-subject variability of the interferon-γ response [5, 6]. The high proportion of conversions and reversions around the 0.35 IU·mL −1 cut-off has led some to suggest that a borderline or equivocal range should be used [7], as this avoids treatment of individuals who do not have a 'stable' positive result, as well as failure to treat those just below the 0.35 threshold who would convert to a positive result if the test were repeated [6]. Borderline and equivocal results for the Quantiferon Gold test are common and repeated borderline tests often change http://ow.ly/PDDZ30fqJ1c